Results - Moloney, Colm; Lawson, John (Scottish Archaeological Internet Reports, 2006)
A detailed archaeological description is organised by phase. Features in Area A were badly truncated and there was a lack of dating absence. They comprised linear features, pits, one of which was stone lined, a possible ring ditch and an 'avenue' of postholes. Features in Area B included a trackway and a large pit of Neolithic or early Bronze Age date. Other noteworthy features included a large stone structure in Area F which produced a radiocarbon date in the Iron Age.